Paradigm Transformation in Land Area of Plantation Cultivation Right from Agrarian Basic Law to Job Creation Law - wicaksono, setiawan; Imam Koeswahyono; Iwan Permadi; Hanif Nur Widhiyanti (YURISDIKSI : Jurnal Wacana Hukum dan Sains, 2025)
The regulation of land area for plantation cultivation rights (Hak Guna Usaha/HGU) has changed from 1960 to 2023. Paradigm theory is one of the theories that examines why and what reasons lie behind written regulations. When legal changes occur, a paradigm shift also takes place. This article addresses the issue of what paradigm is used to determine the land area for plantation cultivation rights in several laws and whether a paradigm shift has occurred. A normative research method is chosen to examine the provisions regarding the land area of cultivation rights in four laws. The analysis uses a systematic, conceptual, and historical approach. This study shows a shift in paradigm in the granting of cultivation rights, particularly from 1960, which emphasized social justice, to 2023, which prioritizes economic interests.